2014
DOI: 10.1080/01639374.2014.963776
|View full text |Cite
|
Sign up to set email alerts
|

“What Am I Fighting For?”: Creating a Controlled Vocabulary for Video Game Plot Metadata

Abstract: A video game's plot is one of its defining features, and prior research confirms the importance of plot metadata to users through persona analysis, interviews, and surveys. However, existing organizational systems, including library catalogs, game-related websites, and traditional plot classification systems, do not adequately describe the plot information of video games, in other words, what the game is really about. We attempt to address the issue by creating a controlled vocabulary based on a domain analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A dictionary of video game themes and content could be used to train models to recognize standard video game themes such as “brotherhood” or “friendship.” This could be used to distinguish between one game and another and make conclusions about the contents of those games. Therefore, developing and improving controlled vocabulary for video games' themes (such as Welhouse et al, 2015), may be a reasonable next step for future studies. In this pilot study, we analyzed a small sample data set, looking at one particular game.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dictionary of video game themes and content could be used to train models to recognize standard video game themes such as “brotherhood” or “friendship.” This could be used to distinguish between one game and another and make conclusions about the contents of those games. Therefore, developing and improving controlled vocabulary for video games' themes (such as Welhouse et al, 2015), may be a reasonable next step for future studies. In this pilot study, we analyzed a small sample data set, looking at one particular game.…”
Section: Discussionmentioning
confidence: 99%
“…In this step, the researcher identified that 45 user reviews out of 101 collected reviews discussed plot and narrative related themes. Among these 45 reviews, the researcher further identified sub‐themes and matched them with the terms from existing related literature (Cho, 2019; Cho, Schmalz, Keating, & Lee, 2018; Lee et al, 2017; Welhouse, Lee, & Bancroft, 2015). After iterative processes of revising codes and codebook structure, the finalized codebook (Figure 1) was created.…”
Section: The Dataset Was Used For Text Analysis and Randomly Selected...mentioning
confidence: 99%
“…Strasburger et al (2009) categorized game into six main categories, namely, general leisure, educational games (such as learning and problem-solving), fantasy violence game, human violence games such as violent fantasy ones and nonviolent sports games, which do not depend on fighting or destruction and finally violent sports games, which depend on fighting and destruction. Welhouse et al (2015) attempted to create a controlled vocabulary to represent video games' aboutness. The study suggested that using elements of the description of video games with the metadata elements should provide a way of identifying, discovering and recommending a video game.…”
Section: Electronic Games Cataloging and Classificationmentioning
confidence: 99%
“…Welhouse et al (2015) attempted to create a controlled vocabulary to represent video games’ aboutness. The study suggested that using elements of the description of video games with the metadata elements should provide a way of identifying, discovering and recommending a video game.…”
Section: Introductionmentioning
confidence: 99%
“…45 In another paper on the same project Welhouse, Lee, and Bancroft explained how they used domain analysis to develop a controlled vocabulary for video game plot metadata. 46 Another way to enhance bibliographic records for non-book materials is to provide access to images of the items described. Moore illustrated this practice in a bibliographic record for an anatomical model.…”
Section: Cataloging Tabletop Gamesmentioning
confidence: 99%